Konsep self esteem pada wanita dewasa awal yang mengalami perceraian - Julia Eva Putri; Neviyarni Suhaili; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2022)
The existence of conflict in the household is unavoidable, a prolonged conflict can cause rifts in the household and even divorce. The divorce rate in Indonesia is increasing day by day. On average, those who experience this divorce are early adult women aged 20-40 years. Divorce experienced by women in early adulthood can have negative psychological effects such as feelings of worthlessness (low self-esteem). If not handled properly, of course this will become a new problem such as stress, depression, feeling unaccepted and other negative feelings.